The design and development of the miniaturised active thermography for in-situ inspection of industrial components. - Du, Weixiang (Cranfield University, 2021)
Nondestructive testing (NDT) is a common and reliable method for the detection of surface and subsurface defects. However, due to the increasing integration and complexity of industrial components and systems, the problem of mismatching of size and volume between the existing inspection unit and the targeted object has limited the applicability of NDT techniques. Especially for geometrically intricate systems, the deployment of NDT devices for in-situ inspection has become a major challenge. Addressing the challenge of inaccessibility and inapplicability, this research proposes a miniaturised active thermography (MAT) system, featured with a small-size and low-cost thermal sensor, and a portable optical heat excitation source. A novel spatial resolution enhancement for a thermogram (SRE4T) system, which includes an infrared (IR) sensor, an XY movement stage and a super-resolution image enhancement method, is also proposed to address the low spatial resolution of the miniaturised sensor without upgrading the sensor. Moreover, dedicated data analysis approaches to evaluate defects are proposed considering the degraded signal quality. Compared with existing non-miniaturised inspection systems, the proposed system is evaluated quantitatively and qualitatively by testing samples with different materials, structures, and a variety of defects. An accessibility test is designed and conducted to evaluate the proposed system’s performance to access geometrically intricate space. The results show that the proposed system can work effectively for the degradation assessment of composite laminates, and also has enhanced accessibility and applicability of deployment for geometrically intricate systems and narrow space targets. It is observed that the data quality for composite materials seems to be more reliable and quantifiable than metal due to the relatively low sample rate of the sensor and the high thermal conductivity of the metal component. The SRE4T system can significantly improve the spatial resolution of miniaturised sensors, although it has not been used for active thermography at the present stage. The current miniaturised IR cameras feature low spatial resolution and low Signal-to-Noise Ratio, which leads to the poor performance of most of the current data analysis methods on these sensors. We propose an effective analytics framework including data processing, image processing and feature extraction to reduce the influence of noise and enhance the detectability of damage.
Addepalli, Pavan - Associate Supervisor
Keywords: In-situ; in-accessible; miniaturised; active thermography; industrial components; imaging enhancement